COSO ERM DAN PERANAN INTERNAL AUDITOR DALAM PENCEGAHAN FRAUD (Survei pada Internal Auditor di Indonesia) - Yenni Carolina; Joanne Euginia Haneda (Jurnal ASET (Akuntansi Riset), 2022)
Abstract Main Purpose - This study aims to determine and analyze how much the role of internal audit and internal control with the COSO ERM 2017 approach has an effect on preventing fraud (corruption).Method - The data was obtained through the distribution of questionnaires to the internal auditors at the Indonesian Institute of Internal Auditors. Determination of the sample using random sampling method, for data analysis used the SEM-PLS analysis method, with the number of samples obtained as many as 133 respondents.Main Findings - The fact that happened in Indonesia, there are several cases of corruption have occurred as an example of the corruption case of PT. Asuransi Jiwasraya (ASABRI), the corruption case of PT. Garuda Indonesia (Persero), Tbk. Corruption case of Lobster Seed permit, case of social assistance covid-19, LPEI corruption allegation. This phenomenon proves that there are still various corruption problems that occur in Indonesia, the 2019 ACFE survey shows that fraud is dominated by acts of corruption with a percentage of 64.4%. This attracts researchers to conduct further research on the role of internal audit and internal control in the COSO ERM 2017 framework which was not found in previous research, and focuses more on preventing fraud, the type of corruption in which more and more cases of corruption appear as stated by ACFE (2019).Theory and Practical Implications - The role of Internal Audit has a positive effect on Fraud Prevention.. Internal Control with the COSO ERM 2017 framework has a positive effect on Fraud Prevention. Novelty - Research on the role of internal audit related to internal control COSO ERM 2017, is still rarely done. In addition, this research also focuses more on preventing fraud in the form of corruption. According to ACFE, currently corruption is the most common fraud case.